Site-Directed Mutagenesis from Arg195 to His of a Microalgal Putatively Chloroplastidial Glycerol-3-Phosphate Acyltransferase Causes an Increase in Phospholipid Levels in Yeast - Ouyang, Long-Ling; Li, Hui; Yan, Xiao-Jun; Xu, Ji-Lin; Zhou, Zhi-Gang (Frontiers in Plant Science, 2016)
To analyze the contribution of glycerol-3-phosphate acyltransferase (GPAT) to the first acylation of glycerol-3-phosphate (G-3-P), the present study focused on a functional analysis of the GPAT gene from Lobosphaera incisa (designated as LiGPAT). A full-length cDNA of LiGPAT consisting of a 1,305-bp ORF, a 1,652-bp 5′-UTR, and a 354-bp 3′-UTR, was cloned. The ORF encoded a 434-amino acid peptide, of which 63 residues at the N-terminus defined a chloroplast transit peptide. Multiple sequence alignment and phylogeny analysis of GPAT homologs provided the convincible bioinformatics evidence that LiGPAT was localized to chloroplasts. Considering the conservation of His among the G-3-P binding sites from chloroplastidial GPATs and the substitution of His by Arg at position 195 in the LiGPAT mature protein (designated mLiGPAT), we established the heterologous expression of either mLiGPAT or its mutant (Arg195His) (sdmLiGPAT) in the GPAT-deficient yeast mutant gat1Δ. Lipid profile analyses of these transgenic yeasts not only validated the acylation function of LiGPAT but also indicated that the site-directed mutagenesis from Arg195 to His led to an increase in the phospholipid level in yeast. Semi-quantitative analysis of mLiGPAT and sdmLiGPAT, together with the structural superimposition of their G-3-P binding sites, indicated that the increased enzymatic activity was caused by the enlarged accessible surface of the phosphate group binding pocket when Arg195 was mutated to His. Thus, the potential of genetic manipulation of GPAT to increase the glycerolipid level in L. incisa and other microalgae would be of great interest.